Experiences of adult cancer patients in a patient navigation program: a qualitative systematic review protocol - Tan, Clarice; Wilson, Sally; McConigley, Ruth (Joanna Briggs Institute, 2014)
Review question. The aim of the project is to conduct a comprehensive review of scholarly literature detailing the experiences of adult cancer patients in patient navigation programs. The specific questions are: 1) What are the experiences of patients with cancer in patient navigation programs? 2) How do patient navigators impact the challenges patients encounter in the cancer care continuum? Inclusion criteria. Types of participants: The types of participants of interest are adult cancer patients aged 18 years and over who are receiving or have received standard cancer care, for example, chemotherapy, radiation therapy and/or hormonal therapy and are in a patient navigation program or had been in a hospital patient navigation program. Exclusion criteria. Studies examining patient navigation programs targeted at the following will be excluded: improving screening rates for cancer, timeliness from positive screening to diagnosis and recruitment and retention for clinical trials, because the patients will not have experienced the complexities of the healthcare system at this point and thus have not had relevant experience. Types of intervention(s)/phenomena of interest. The phenomena of interest are the experiences of adult cancer patients who used patient navigation programs in hospital and the impact of patient navigators on the challenges the patients encountered in the cancer care continuum.